Mechanical Behavior of Normal Concrete Reinforced with Kantharo Suter Fiber - Syed Iftikhar Ahmed; Fahad Ali Shaikh; Sadam Hussain Jakhrani; Muhammad Yousaf Mushtaq; Junaid Ahmad Sidiqy (Salehan Institute of Higher Education, 2017)
Physical characteristics of concrete can be enhanced by addition of different materials in various proportions. Fibrous substances, such as, steel, synthetic, glass, and natural fibers not only increase the structural and tensile strength but also cohesion of concrete by overcoming micro cracks and deficiencies in concrete. In this study, the effect of Kantharo suter fibers (animal hair) on compressive, flexural and split tensile strength, and workability of plain concrete was determined. For that, experiments were conducted on concrete cubes, beams and cylinders by adding different proportions of Kantharo suter fibers from 0.125 to 1.0 percentage by weight of cement. In each proportion of Kantharo suter fibers, three cubes, three cylinders and one beam were casted and cured for 28 days. The acquired results were compared with the plain cement concrete specimens. It was discovered from the results that 0.375 percentages of Kantharo suter fibers in normal concrete was optimum by weight of cement. The strength parameters and slump of concrete showed better results than control mixes even without using any admixture in the specimens. This study could also be enhanced using combinations of different fibers and other admixtures.